Sexuality and Management of Benign Prostatic Hyperplasia with Alfuzosin: SAMBA Thailand - Somboon Leungwattanakij (2018)
Introduction: Benign prostatic hyperplasia (BPH) is a common condition among elderly men. The aim of therapy is to improve lower urinary tract symptoms (LUTS) and quality of life (QoL) and to prevent complications. Aim: The primary objective was to assess the effect on ejaculatory dysfunction (EjD) of 6 months treatment with alfuzosin (XATRAL) 10 mg once daily (OD) in men with LUTS suggestive of BPH in Thailand. Secondary objectives were to evaluate the efficacy of alfuzosin on LUTS, bother score (International Prostate Symptom Score [IPSS] 8th question), erectile dysfunction (ED), onset of action, and tolerability. Methods: Overall, 99 men with moderate to severe LUTS suggestive of BPH (mean IPSS 18.9, bother score 4.3) were enrolled in an open-label study. Sexual function was evaluated at baseline and after 6 months treatment, using the International Index of Erectile Function-5 and the Male Sexual Health Questionnaire (MSHQ) ejaculation score, a new validated questionnaire assessing seven EjD symptoms. Main Outcome Measure: The main outcome measure is mean change from baseline to the end of treatment in the MSHQ Ejaculation score. Results: MHSQ ejaculation score significantly improved from 23.09 at baseline to 21.54 at 6 months (P = 0.022). Overall, 70% of patients perceived an improvement in LUTS within 1 week (36.3% within 3 days). IPSS total score significantly improved from 18.93 at baseline to 9.59 at 6 months (P < 0.001). IPSS voiding and irritative subscores also significantly improved. The percentage of patients with moderate or severe ED decreased from 35.3% at baseline to 21.8% at 6 months. Most adverse events were dizziness (3%) and orthostatic hypotension (1%) with minor intensity. No significant change in blood pressure and heart rate was observed. Conclusions: Alfuzosin 10 mg OD administered for 6 months provides a marked and rapid (within 1 week) improvement in LUTS and bother score while improving both ED and EjD. © 2010 International Society for Sexual Medicine.